Electrophoretic fingerprint metallothionein analysis as a potential prostate cancer biomarker - Krizkova, Sona; Ryvolova, Marketa; Gumulec, Jaromir; Masarik, Michal; Adam, Vojtech; Majzlik, Petr; Hubalek, Jaromir; Provaznik, Ivo; Kizek, Rene (Electrophoresis, 2011)
Prostate-specific antigen (PSA) is a routinely used marker of prostate cancer; however, the cut-off values for unambiguous positive/negative prostate cancer diagnoses are not defined. Therefore, despite the best effort, certain percentage of misdiagnosed cases is being recorded every year. For this reason, search for more specific diagnostic markers is of great interest. In this study, systematic comparison of PSA and metallothionein (MT) levels in blood serum of 46 prostate cancer-diagnosed patients is presented. It is clearly demonstrated that PSA levels vary significantly and despite normal total PSA values in the range of 0 - 4 ng/mL were obtained in over 36.9% of cases, positive prostate cancer was diagnosed by biopsy. In contrary, MT levels were considerably elevated in all tested samples and no significant variations were observed. These results are indicating the potential of MT as an additional prostate cancer marker reducing, in combination with PSA, the probability of false positive/negative diagnosis. To increase the throughput of the screening, chip-based capillary electrophoresis was suggested as a rapid and effective method for the fingerprinting analysis of prostate cancer from diseased blood sera.
Keywords: Prostatic Neoplasms; Electrophoresis, Polyacrylamide Gel; nádory prostaty; Carcinoma, Acinar Cell; Humans; elektroforéza v polyakrylamidovém gelu; lidé středního věku; Sulfhydryl Compounds; kohortové studie; Biomarkers, Tumor; Electrophoresis, Capillary; Predictive Value of Tests; Aged; Blotting, Western; Prostate-Specific Antigen; senioři; lidé; Metallothionein; Glutathione; elektroforéza kapilární; Cohort Studies; nádorové biomarkery; Male; Middle Aged; prediktivní hodnota testů; prostatický specifický antigen; glutathion; sulfhydrylové sloučeniny; metalothionein; western blotting; mužské pohlaví; acinární karcinom